Practicality of Authentic Instruments Computer Competency Assessment for Students of Vocational High School - Elsa Firdianis; Ambiyar Ambiyar; Wakhinuddin Wakhinuddin; M. Iksan Ardiyansyah; Yumn Jamilah (Postgraduate School, Universitas Negeri Padang, 2020)
This study aims to develop authentic instruments in the assessment of Digital simulations to measure student learning skills that are practical and effective. This research uses Research and Development with ADDIE development models. Through the stages of analysis (analysis), design (design), development (development), implementation (implementation), evaluation (evaluation). The research subjects were students of class X SMK Negeri 05 Padang, digital simulation subjects. The research data was obtained through validation instrument sheets, practical questionnaires, and observations. The practicality test results show that the authentic assessment that was developed was very practical with the percentage of practicality of teachers on lesson plans being 88.3% and authentic assessments at 82.3%. This developmental research produced an authentic practical and effective assessment instrument that can be used by teachers in assessing students' skills in school in the learning process.